Refinement of turbulent flow velocity characteristics - Y.V. Bryanskaya (Инженерно-строительный журнал, 2013)
The basic laws of Prandtl semi-empirical turbulence theory were analyzed in the article. It was shown, that the Prandtl – Nikuradse logarithmic distribution of velocities are not strictly universal. The change of the first and second turbulence constants was analyzed on the basis of experimental data of I. Nikuradse. The logarithmic velocity profiles for smooth and rough pipes have been transformed. A united velocity logarithmic profile for flows in pipes, appropriate for any rate of hydraulic resistance was received. A more precise, consistent with the resistance laws, description of the kinematic structure of the flow with varying parameters of the velocity profiles was set. It was shown that the position of the average velocity point for the flow in pipe remained constant when the parameters of the velocity profile changed.